OCCURRENCE OF PHYTOPHAGOUS SCARABAEIDAE (INSECTA: COLEOPTERA) LARVAE IN DIFFERENT SUCCESSION CROP SYSTEMS - Rodrigues, Sérgio Roberto (2011)
Information about Scarabaeidae phytophagous are still rare for the Center-West Region of Brazil. Thus, in the experimental area of the Universidade Estadual do Mato Grosso do Sul, in Aquidauana, Mato Grosso do Sul State, Brazil, the succession of soybean, maize, and forage turnip was sowed from February 2004 to October 2005, when the larvae population dynamics was evaluated. From October 2006 to May 2008, nine succession systems were sowed, the larval density evaluated, and the identification of the current species was carried out. When the larvae were sampled for soybean, in January 2005 and 2006, the highest densities were found in the field (3.44 larvae m-2 and 4.19 larvae m-2, respectively). The forage turnip, sampled in October 2004 and 2005, showed the lowest densities (0.03 larvae m-2 and 0.02 larvae m-2, respectively). In the crop succession systems, the following species were found: Liogenys fuscus Blanchard (highest amount), Liogenys bidenticeps Moser, Anomala testaceipennis Blanchard, Paranomala inconstans (Burmeister), Geniates borelli Camerano, Cyclocephala forsteri Endrodi, Cyclocephala verticalis Burmeister, and Phyllophaga sp. For the succession systems with maize sowed at the traditional season, the highest larval densities were found, specially favoring the development of L. fuscus, while the succession systems with soybean, maize, and under fallow, and soybean, crotalaria, and forage turnip, as well as the three systems with cotton-plant, did not favor it.KEY-WORDS: Zea mays; Glycine max; Raphanus sativus; soil pests; larvae density.